RANCANG BANGUN APLIKASI PENJUALAN KHUSUS RESELLERPADA TOKO VPM COLLECTION - Vanessya Putri Utami (2023)
The development of information technology is very rapid, including the many online media to increase sales, so that online stores are the right and easy choice for buying and selling transactions. The VPM Collection store is an online store in the form of Muslim fashion products that still use social media in sales transactions. This causes a lack of accurate information on Muslim fashion products at the VPM Collection Store, sales data processing is still in the form of manual notes using paper and the ordering process via whatsapp media. Based on this, the author will design and also build a website-based information system to make it easier for resellers to register, view catalogs and find out the amount of stock in realtime, then resellers can transact and finally the admin will confirm orders.the author uses the Waterfall Method with problem identification using the PIECES Method, PHP programming language using the codeigniter framework, the database used is MySQL and ends with a trial test using black box testing.